VOLATILITY TRANSMISSION BETWEEN US ECONOMIC POLICY UNCERTAINTY AND BIST (BORSA ISTANBUL) MAJOR SECTOR INDICES - KOCAARSLAN, Barış (Business & Management Studies: An International Journal, 2020)
The significant effects of global economic policy uncertainties on world markets have been revealed in the related literature recently. The primary purpose of this study is to examine the volatility interaction (the causality in variance relationship) between uncertainty in US economic policies and BIST (Borsa Istanbul) major sector indices (financial, industrial, and technology indices). To satisfy this purpose, the causality in variance approach proposed by Hafner and Herwartz (2006) is utilized. The findings of the implemented volatility model show that the US economic policy uncertainty and BIST (Borsa Istanbul) major sector indices are strongly influenced by long-term volatility. According to the main findings of the causality invariance test, it is observed that there are significant and robust volatility transmissions from the US economic policy uncertainty to the BIST significant sector returns (financial, industrial, and technology sector returns). The test findings indicate that the BIST significant sector returns are quite sensitive to shocks in the US economic policy uncertainty. The results of the analysis present considerable implications for market participants in terms of developing effective economic policies and constructing optimal portfolios.